Anxiety and Depression Among Sexual Minority Women and Men in Sweden: Is the Risk Equally Spread Within the Sexual Minority Population?. Issue 3 (12th February 2017) - Björkenstam, Charlotte; Björkenstam, Emma; Andersson, Gunnar; Cochran, Susan; Kosidou, Kyriaki
Abstract: Introduction: Sexual minority individuals have a higher risk of anxiety and depression compared with heterosexuals. However, whether the higher risk is spread equally across the sexual minority population is not clear. Aim: To investigate the association between sexual orientation and self-reported current anxiety and a history of diagnosis of depression, paying particular attention to possible subgroup differences in risks within the sexual minority population, stratified by sex and to examine participants' history of medical care for anxiety disorders and depression. Methods: We conducted a population-based study of 874 lesbians and gays, 841 bisexuals, and 67, 980 heterosexuals recruited in 2010 in Stockholm County. Data were obtained from self-administered surveys that were linked to nationwide registers. Main Outcome Measures: By using logistic regression, we compared risks of current anxiety, histories of diagnosed depression, and register-based medical care for anxiety and/or depression in lesbian and gay, bisexual, and heterosexual individuals. Results: Bisexual women and gay men were more likely to report anxiety compared with their heterosexual peers. Bisexual individuals and gay men also were more likely to report a past diagnosis of depression. All sexual minority groups had an increased risk of having used medical care for anxiety and depression compared with heterosexuals, with bisexual women having the highest risk. Conclusion: Bisexual women appear to be a particularly vulnerable sexual minority group. Advocating for non-discrimination and protections for lesbian, gay, and bisexual people is a logical extension of the effort to lower the prevalence of mental illness.